ПРИНЦИПИ ПРАВА В РОЗВ’ЯЗАННІ ЮРИДИЧНИХ КОЛІЗІЙ - Корнієнко, Михайло Васильович, Тертишник Володимир Митрофанович (SUPREMANCE OF LAW, 2017)
The article reveals the notion of a system of law, especially the principles of proportionality, legal certainty, legal fi ction, has problems and competition legal standards, harmonization of legislation based on principles of law.